Down-regulation of Hsp27 (HSPB1) in MCF-7 human breast cancer cells induces up-regulation of PTEN - Cayado Gutiérrez, Niubys de Los Milagros (2013)
Hsp27 (HSPB1) is usually overexpressed in breast cancers affecting the disease outcome and the sensitivity of tumors to chemotherapy and radiotherapy. Hsp27 interacts with other proteins such as β-catenin, histone deacetylase HDAC6, transcription factor STAT2 and procaspase-3. Phosphatase and tensin homologue (PTEN) is a tumor suppressor gene that is deleted in many human tumors. The PI3K/Akt signaling pathway is negatively regulated by PTEN. Hsp27 is described as a key component of the Akt signaling cascade: Akt, BAD, Forkhead transcription factors, Hsp27, mitogen-activated protein kinase kinase-3 and -6. Here, we have examined whether the downregulation of Hsp27 by siHsp27 affects the PTEN levels in the MCF-7 human breast cancer cell line. PTEN was detected with two different antibodies using western blots and immunocytochemistry. p-Akt was also evaluated by western blot. In addition, Hsp27 and PTEN were immunoprecipitated to know whether these proteins interact. Intracellular colocalization studies were carried out by confocal microscopy. A significant reduction in the Hsp27 levels was noted in the siHsp27 transfected cells. These Hsp27 downregulated cells showed a significant increased expression of PTEN. The MW 76 and 55 kDa PTEN forms were upregulated as revealed by two different antibodies. The phosphatase activity of PTEN seems to be active because p-Akt levels were reduced. Hsp27 immunoprecipitation was bringing PTEN and vice versa, these two proteins seem to interact at cytoplasmic level by FRET. Downregulation of Hsp27 stabilized PTEN protein levels. Chaperone-assisted E3 ligase C terminus of Hsc70-interacting protein (CHIP) levels were not significantly influenced by Hsp27 downregulation. In conclusion, we report a novel function of Hsp27 modulating the PTEN levels in human breast cancer cells suggesting an interaction between these two molecules.